Effect of Group Exercising and Adjusting the Brace at Shorter Intervals on Cobb Angle and Quality of Life of Patients With Idiopathic Scoliosis. (February 2018) - Hedayati, Zahra; Ahmadi, Amir; Kamyab, Mojtaba; Babaee, Taher; Ganjavian, Mohammad Saleh
Abstract : Objective: The aim of the study was to evaluate the effect of group exercise with brace adjustment at shorter intervals than used in routine practice in late-onset idiopathic scoliosis patients. Design: This was a quasi-experimental study. Thirty patients with progressive scoliosis curves of 15–50 degrees and a prescription for a brace were divided into experimental and control groups, both of which participated in an 11-wk treatment program. Those in the experimental group underwent brace adjustment twice per week and performed group exercise, whereas those in the control group received a routine protocol. The quality of life and Cobb angle of patients in both groups were evaluated based on baseline and final results of the 22-item Scoliosis Research Society questionnaire and primary and secondary radiographs. Results: In the experimental group, the improvement in Cobb angle and patient satisfaction was greater than that in the control group ( P < 0.05). Moreover, in patients with Cobb angles of less than 30 degrees, the self-image and satisfaction domains and the total scores of patients in the experimental group were significantly different from those in the control group at the final assessment ( P < 0.05). Conclusions: Brace adjustment at shorter intervals combined with group exercise increases patient satisfaction and reduces scoliosis Cobb angles.